Pengaruh Pelatihan Dan Pengembangan Sumber Daya Manusia Terhadap Kinerja Karyawan Pada Rumah Sakit Sentra Medika Cibinong - Dwi Astuti Alawiyah (CV. ITTC INDONESIA, 2025)
This study aims to determine the effect of training and human resource development on employee performance at Sentra Medika Cibinong Hospital. The population and research sample were 97 respondents. The sampling technique used Random Sample and Quota Sample techniques. Data processing in this study using the SPSS (Statistical Package for Social Science) software programme version 26.0. The research method uses a type of quantitative method research through an associative approach. The results of the research on the Training variable (X1) show the results that there is an effect of training on employee performance at Sentra Medika Cibinong Hospital. Based on the results of the t test (partial test) which shows the value of t count> t table and significant <0.05, namely; 2.958> 1.985 and significant 0.004 <0.05. In the Human Resource Development variable (X2) shows the results there is an influence of human resource development on employee performance at Sentra Medika Cibinong Hospital. Based on the results of the t test (partial test) which shows the value of t count> t table and significant <0.05, namely; 3.684> 1.985 significant 0.000 <0.05. Simultaneously shows the results of the effect of training and human resource development on employee performance at Sentra Medika Cibinong Hospital. Based on the results of the F test (simultaneous test) which shows the value of F count> F table and significant <0.05, namely; 24,721> 3.09 significant 0.000 <0.05.